Community Pharmacy-Delivered Interventions for Nutrition and Diet-Related Health Promotion - Gizem Acar; Rachael Frost; Sukvinder Kaur Bhamra; Michael Heinrich (Proceedings)
Background: The growing burden of nutrition-related non-communicable diseases (NCDs) across the life course is a major public health concern which needs to be addressed. Unhealthy diets are the number one risk factor for NCD-related morbidity and mortality, and along with obesity and nutrition-related chronic diseases, they are closely associated with food systems. Pharmacists are in a unique position to play an integral role in food systems transformation through educating people about modifiable behaviours such as dietary practices and healthy lifestyles. They can make an important contribution to improve public health nutrition and potentially impact the rising epidemic of obesity and diet-related NCDs through specific interventions, services, and education. This study aimed to complete a scoping review of studies of pharmacist-delivered interventions for nutrition- and diet-related health promotion. Methods: A comprehensive literature search was conducted on electronic databases Medline and Embase from 2001 to 2022. Pharmacist-led interventions, including a nutrition component with the aim of improving health and nutrition behaviours, and NCDs management studies with lifestyle and nutrition behaviour change components, were eligible. Results: A total of 1244 studies were identified, and 16 studies met the criteria for inclusion. Studies included interventions for weight management, type 2 diabetes, cardiovascular health, and health education. The key components of the interventions were a combination of health and dietary education, nutritional follow-up, behaviour change through tailored counselling, goal setting, and action planning. Weight management interventions resulted in positive effects on anthropometric measures and dietary behaviour change. Interventions for the management of chronic conditions resulted with clinically significant improvement in patients’ HbA1c, cholesterol, and blood pressure levels. Conclusions: The role of pharmacists is expanding beyond their traditional roles to a broader goal of delivering a range of health promotion interventions. The evidence in this review demonstrates that nutrition-related interventions in the pharmacy setting have the potential to improve both anthropometric and clinical outcomes, as well as result in dietary behaviour change. This review highlights the need for interventions that will address nutrition and dietary health goals with a “systems thinking” and a holistic life-course approach to health and food systems.